Canopy Position Affect Rind Biochemical Properties of 'Marsh' Grapefruit during Postharvest Cold Storage at Non-chilling Temperature. (14th September 2020) - Olarewaju, Olaoluwa Omoniyi; Magwaza, Lembe Samukelo; Fawole, Olaniyi Amos; Tesfay, Samson Zeray; Opara, Umezuruike Linus
ABSTRACT: Effect of canopy position on rind biochemical properties of 'Marsh' grapefruit during postharvest non-chilling cold storage was evaluated on fruit harvested from different orchard locations. Inside canopy (IC) and outside canopy (OC) fruits were harvested at commercial maturity from two commercial farms located at KwaZulu-Natal (KZN) and Limpopo (LMP), South Africa, during two seasons. Rind biochemical analyses including color indices, total phenolic concentration, and sugars were performed on harvested grapefruit after Weeks 0, 3, 6, and 9 of cold storage at 7.5 ± 0.5°C. Canopy position showed a high significant ( p < .001) effect on rind biochemicals while significant ( p < .05) influence of orchard locations was observed on the same parameters. Reducing sugars were more concentrated in IC fruit harvested from both orchard location than OC fruit at Weeks 0 and 3, but inverse results occurred at Weeks 6 and 9. Orchard location significantly ( p < .001) influenced vitamin C (14.4, 14.2, 14.4, 14.8 g kg −1 ) and (12.3, 16.1, 15.9, 14.6 g kg −1 ) of fruit rind at Weeks 0, 3, 6, and 9 from KZN and LMP, respectively. This study revealed that canopy position can influence rind biochemical properties of 'Marsh' grapefruit during non-chilling postharvest cold storage. However, further studies are required to formulate and provide the citrus industries with adequate advice.